Choices and Consequences: Recommendations for an Improved Understanding of Cultural Distance in International Marketing Research. Issue 3 (September 2021) - Griffith, David A.; Dean, Tereza; Hoppner, Jessica J.
Cultural distance is an important element in the study of international marketing phenomena. However, scholars have voiced significant concerns with its use. Although reviews of cultural distance have been conducted, no research has yet directly addressed how the choices that scholars make in relation to the conceptualization and operationalization of cultural distance influence our understanding of its role in international marketing phenomena. In this work, the authors review concerns pertaining to cultural distance and use them as a foundation to systematically analyze 83 articles referencing cultural distance in the international marketing literature to understand the choices that have been made. They find significant heterogeneity in conceptualization and operationalization of cultural distance. Then, they examine the empirical consequences of this choice heterogeneity within a single data set of 148 suppliers to a European original equipment manufacturer. The findings demonstrate that differences in conceptualizations and operationalizations significantly influence the observed effects of cultural distance and, thus, the understanding of its role in international marketing phenomena. Last, the authors put forth a series of recommendations aimed to enhance the discipline's ability to build a strong foundation of knowledge of cultural distance's role in international marketing phenomena.